School governance in Nepal: A perspective of new public management theory - Adhikari, Devendra (Journal of Management and Development Studies, 2022)
School Management Committees have the tasks to maintain good governance of public schools in Nepal. The School Management Committees are driven by the New Public Management theory. The theory advocates for the transformation of public administration into public management which began in Nepal in 1990 A.D. and has continued thereafter. The purpose of this article is to identify the changes in the application of New Public Management theory in school governance through the perspective of power-sharing between communities and local governments. In this study, I have applied the narrative policy review method to gather evidences and enrich the discussion. I have presented some discussion notes to show that the School Management Committee model was practiced with the engagements of parents and communities from 2003 to 2016 A.D. After 2015, the active role of the parents and communities in school governance was shifted to the jurisdiction of local governments, which I have concluded as an alteration in the New Public Management model. I recommend that the core and leading engagement of parents and communities in school governance should be ensured for the good governance of schools in Nepal, in which local governments can act as a watchdog. The study, carried out based on New Public Management theoretical referent, is helpful to scholars to understand the change in the application of New Public Management theory through the perspective of school governance in Nepal.